Pengaruh Variasi Fotoperiodisitas terhadap Pertumbuhan Chlorella dalam Medium Basal Bold - Nining Prihantini; Winny Rachmayanti; Wisnu Wardhana (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
The research of photoperiodicity effect on the cell densities of genus Chlorella grown in Bold’s Basal Medium (BBM) had been done. Observations were done for 14 days. Research was experimental study with full random design to 8 varieties of photoperiodicity i.e. 6 h light/18 h dark (L/D) cycles, 8 h light/16 h dark (L/D) cycles, 10 h light/14 h dark (L/D) cycles, 12 h light/12 h dark (L/D) cycles, 14 h light/10 h dark (L/D) cycles, 16 h light/8 h dark (L/D) cycles, 18 h light/6 h dark (L/D) cycles, and 24 h light/0 h dark (L/D) cycles. On peak culture, 24 h light/0 h dark (L/D) cycles produced the highest cell numbers (204.680.000 cell/ml) and the lowest cell numbers were achieved by culture with 6 h light/18 h dark (L/D) cycles. Kruskall-Wallis test showed that there were some effects of photoperiodicity variations on cell numbers of Chlorella (cell/ml) in culture (p>0.05). Multiple comparison tests showed that mean of cell numbers of Chlorella (cell/ml) differ (p>0.01) on every photoperiodicity. Relationship between photoperiodicity and cell numbers of Chlorella was determined by regression equation Ŷ = 24634821,214 + 21977643,869 X.